A Dynamics Approach to the Computation of Eigenvectors of Matrices (Journal of Computational Mathematics, 2021)
We construct a family of dynamical systems whose evolution converges to the eigenvectors of a general square matrix, not necessarily symmetric. We analyze the convergence of those systems and perform numerical tests. Some examples and comparisons with the power methods are presented.